Knowledge activism by CPAs in public sector organisations / Dennis W. Taylor - Taylor, Dennis W. (Faculty of Accountancy & Accounting Research Institute (ARI), 2004)
Structural reforms in the public sector during the past two decades have given accounting professionals more central roles in knowledge management in the sector. This study focuses on the knowledge activism of members of CPA Australia who hold senior and top positions in Australian public sector entities at federal, state or local government levels. Von Krogh et al. s (1997) dimensions of knowledge activism - knowledge catalyst, connector and merchant of foresight - are operationalised in this study. Through a survey of CPAs working in senior / top positions in the public sector, a description is first provided of their levels of knowledge activism. Findings are then presented on tests of hypothesized relationships between public sector entities' internal aspects of information consciousness and accountability-orientation, as contextual variables, and the extent of engagement of CPAs in knowledge activism, particularly the role of knowledge connector. Results of this study provide insights into the knowledge activism of accountants working in various types of public sector entities and presents preliminary evidence of factors influencing this activity.